2020
DOI: 10.1093/pubmed/fdaa221
|View full text |Cite
|
Sign up to set email alerts
|

HIV- and hypertension-related knowledge and medication adherence in HIV seropositive persons with hypertension

Abstract: Background There is increasing prevalence of diseases associated with ageing such as hypertension, among people living with HIV (PLWHV). This study sought to assess: (1) knowledge related to HIV infection and hypertension, (2) adherence to prescribed medications and (3) clinical outcomes among HIV-positive persons with hypertension at a Nigerian hospital. Methods The Patient’s HIV Knowledge Questionnaire (PHKQ), Hypertension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The reasons for the exclusion of papers are noted in Figure 1. In total, 82 articles [27–108] were found to be eligible and data were then extracted (Supplementary Material 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the exclusion of papers are noted in Figure 1. In total, 82 articles [27–108] were found to be eligible and data were then extracted (Supplementary Material 4).…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for the exclusion of papers are noted in Figure 1 . In total, 82 articles [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ,…”
Section: Resultsmentioning
confidence: 99%
“…In spite of this, data suggest that hypertensive PLWHV receive sub‐optimal hypertension care 10 . Moreover, although PLWHV have regular and routine access to health care, several studies have shown that rates of BP control are low in those with coexisting hypertension, 11–15 indicating possible one‐dimensional focus of care in HIV clinics 10…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…An important cause of poor BP control is poor adherence to antihypertensive drugs 16 which could be due to a myriad of reasons. In PLWHV, management of comorbidities is often relegated 17 ; antiretroviral medications are usually regarded as being more important than medications for hypertension, resulting in better adherence to the former 12,18,19 . Furthermore, the potential for drug‐drug interaction is higher in multimorbidity 20,21 ; such interactions have been adduced to explain clinical failure of antiretroviral therapy 21 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation